1986
DOI: 10.1007/bf02133781
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between umbilical vein blood flow and umbilical blood viscosity in normal and complicated pregnancies

Abstract: Umbilical vein blood flow (UVBF) was studied during the last 24 h before delivery using a combination of real-time and Doppler ultrasonic equipment in 64 normal and pathological pregnancies and the results were correlated with the values of whole blood viscosity taken from the umbilical vein after delivery. UVBF was reduced in the subgroup with chronic fetal distress (n = 14) (P less than 0.001) and the hypertensive pregnancies (n = 17) (P less than 0.05), whereas umbilical blood viscosity was increased only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Although blood flow velocity measurements are difficult to correctly obtain, it seems that in IUGR fetuses the umbilical blood flow velocity increase normally present in healthy fetuses with advancing gestation does not occur (10). The result of the present study agrees with those of Ferrazzi et al (11) and of Jouppila et al (24), who found that IUGR fetuses had a lower mean umbilical vein blood flow velocity than AGA fetuses.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although blood flow velocity measurements are difficult to correctly obtain, it seems that in IUGR fetuses the umbilical blood flow velocity increase normally present in healthy fetuses with advancing gestation does not occur (10). The result of the present study agrees with those of Ferrazzi et al (11) and of Jouppila et al (24), who found that IUGR fetuses had a lower mean umbilical vein blood flow velocity than AGA fetuses.…”
Section: Discussionsupporting
confidence: 94%
“…A possible explanation for the reduced umbilical vein blood velocity in IUGR fetuses is the different blood viscosity between these fetuses and AGA fetuses. Jouppila et al (24) reported that an inverse correlation exists between umbilical vein blood viscosity and both umbilical blood flow volume and velocity. Furthermore, these authors found that umbilical cord blood viscosity is significantly increased in IUGR fetuses without maternal or fetal diseases compared with AGA fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…The chosen viscosity value is close to the foetal one, which is higher than that in the adult circulation due to higher haematocrit (Jouppila et al, 1986;El Bouhmadi et al, 2000). HLHS patients are operated in the first days after delivery as this pathology is not compatible with life.…”
Section: Article In Pressmentioning
confidence: 96%
“…The first harmonic of this calculated pressure, corresponding to the fundamental frequency, was imposed as the BC at the DV inlet. The blood was assumed to have a density ρ = 1.05 × 10 3 kg/m 3 (Fernandez et al 1976) and a dynamic viscosity of µ = 4.2 × 10 −3 kg/ms (Jouppila et al 1986). Further details on the numerical implementation may be found in the Appendix A.…”
Section: Numerical Implementationmentioning
confidence: 99%